Digital Promotion in Increasing Business Activities for the Distinctive Excellence Tempe Chips in Purwokerto - Intan Shaferi; Alisa Tri Nawarini; Rio Dhani Laksana; Ary Yunanto (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Business activities in MSME-scale businesses still need to be improved. This is because business activities are not just about selling, but how manage a business so that the dynamics of activities continue to run in line with the ongoing economic  conditions. Promotion is an activity that must always be carried out, considering that the purpose is not only to introduce new products but also as a reminder for consumers and the public of the existence of the product. Tempeh chips are a traditional regional food, where this peculiarity needs to be promoted. Without business activities that carry digital promotion, currently MSMEs that produced tempeh chips can be left behind. Therefore, the use of the unique characteristic advantages of chips can be used to promote products while introducing the potential of the local area. Tempeh chips in Purwokerto have their own taste peculiarities because they are made original and still carry the concept of traditional food chips so that their authenticity is still maintained for their characteristic taste. This community service program partner is an MSME partner where production is produced, but it still needs efforts in terms of consistency in product introduction and also self-existence. This is because production of partner also supports other brands as suppliers. So that, digital promotion is hoped that it will add to the advantages of partner tempeh chips in Purwokerto and can provide better sales and income. The methods that will be used in this service program include problem identification, discussions with partners, providing business training which includes digital marketing and promotion with digital media and market place platforms.